2022
DOI: 10.2147/ndt.s368471
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Serum Uric Acid Levels and Suicide Attempts in Adolescents and Young Adults with Major Depressive Disorder: A Retrospective Study

Abstract: Purpose Uric acid (UA) is thought to exert neuroprotective roles. The purpose of this study was to examine the association of serum UA with suicide attempts (SA) in adolescents and young adults with major depressive disorder (MDD). Patients and Methods We retrospectively recruited 533 participants with MDD aged 13 to 25 years, of which 168 had a history of SA in the past three months and 365 did not have a history of SA. Serum UA levels were measured using the uricase-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…In addition, our previous study has shown that lower serum uric acid levels have a significant relationship with female’s suicide risk. 59 Suicide and self-injury have common characteristics in some aspects. Therefore, we speculate that UA, an important antioxidant factor, may participate in the pathological mechanism of female suicide and self-injury at the same time.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, our previous study has shown that lower serum uric acid levels have a significant relationship with female’s suicide risk. 59 Suicide and self-injury have common characteristics in some aspects. Therefore, we speculate that UA, an important antioxidant factor, may participate in the pathological mechanism of female suicide and self-injury at the same time.…”
Section: Discussionmentioning
confidence: 99%